2019
DOI: 10.1002/hbm.24709
|View full text |Cite
|
Sign up to set email alerts
|

Shifting brain circuits in pain chronicity

Abstract: The evaluation of brain changes to a specific pain condition in pediatric and adult patients allows for insights into potential mechanisms of pain chronicity and possibly long‐term brain changes. Here we focused on the primary somatosensory system (SS) involved in pain processing, namely the ventroposterolateral thalamus (VPL) and the primary somatosensory cortex (SI). We evaluated, using MRI, three specific processes: (a) somatotopy of changes in the SS for different pain origins (viz., foot vs. arm); (b) dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…This is supported by extracted features that show how inflammatory molecules relating to cell cycle and the stress response (Rosati et al, 2011) as well as brain regions implicated in sensory integration (superior longitudinal fasciculus (Herbet et al, 2018)) and the adaptation to chronic stressors such as pain (Caudate (Wunderlich et al, 2011)) were the highest correlated in the ankle injury cohort. Moreover, recently published work from our lab has shown that regions such as the inferior temporal gyrus and orbitofrontal cortex had a similar increase in acute neuropathic pain patients (Youssef et al, 2019). These same regions were found to further increase in chronic pain patients suggesting a potential for regions identified in this investigation to be implicated in the development of chronic pain.…”
Section: Discussionmentioning
confidence: 87%
“…This is supported by extracted features that show how inflammatory molecules relating to cell cycle and the stress response (Rosati et al, 2011) as well as brain regions implicated in sensory integration (superior longitudinal fasciculus (Herbet et al, 2018)) and the adaptation to chronic stressors such as pain (Caudate (Wunderlich et al, 2011)) were the highest correlated in the ankle injury cohort. Moreover, recently published work from our lab has shown that regions such as the inferior temporal gyrus and orbitofrontal cortex had a similar increase in acute neuropathic pain patients (Youssef et al, 2019). These same regions were found to further increase in chronic pain patients suggesting a potential for regions identified in this investigation to be implicated in the development of chronic pain.…”
Section: Discussionmentioning
confidence: 87%
“…2 Neuroscience research suggests injuries and/or inflammatory processes may trigger change in pain processing in the peripheral and central nervous system (CNS), which is thought to contribute to the development and maintenance of chronic pain. [3][4][5][6][7] One proposed mechanism of the alterations in central pain processing is central sensitization (CS) defined as the amplification of neural signaling within the CNS that elicits pain hypersensitivity. [8][9][10] CS is thought be a predominant characteristic of fibromyalgia, chronic fatigue, irritable bowel syndrome, and chronic whiplash disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This study assumes that there is a common configuration of brain activity that corresponds to pain representation, that it can be measured using BOLD fMRI, and that incremental reconfigurations of this activity correspond to proportional changes in subjective experience. However, distinct representations have been demonstrated for different types of pain including somatosensory and vicarious pain [ 45 ] and different kinds of clinical pain [ 46 , 47 ]. Further, BOLD fMRI is best at measuring the anatomical configuration of responses [ 48 ], but the absolute magnitude of evoked activity also encodes pain information [ 26 ].…”
Section: Discussionmentioning
confidence: 99%